Martin Bucer and the Problem of Tolerance - Kroon, Marijn de (The sixteenth century journal, 1988)
From the roots of Bucer's theology, characterized by the basic concepts of piety and resonableness epieikeia, come powerful impulses toward openness and tolerance. These impulses must be analyzed in categories of the "internal" and the "external." The influence of his theological latitude may be seen in his views on marriage and divorce in the area of church discipline and in his behavior toward dissidents, where Erasmian attitudes may be discerned.